Photodynamic Therapy As Adjunctive Therapy In Patients With Periodontitis Accompanied By Diabetes. A Scoping Review - Nida Ul Azkiya; Hanna Adianita; Ira Komara; Chandra Andi Bawono (Fakultas Kedokteran Gigi, Universitas Mahasaraswati Denpasar, 2025)
Introduction: Periodontitis is a multifactorial disease that causes inflammation and affects the tooth-supporting tissues, characterized by loss of periodontal tissue attachment and bone destruction. The main cause of periodontitis is periopathogenic bacteria, but systemic conditions can be risk factors for the development and severity of periodontal disorders. This study aimed to describe the effect of photodynamic therapy as an adjunctive therapy for periodontitis patients with diabetes. Review: Diabetes mellitus (DM) and periodontitis are complex diseases with a bidirectional relationship, and can increase the risk of periodontitis and periodontal inflammation affecting glycemic control. This study is a literature review using the scoping review method, with a systematic approach to map, analyze, and summarize previous research evidence. The article search used Pubmed, ScienceDirect, EBSCOhost, Researchgate, and Taylor and Francis Online databases from 2013 to 2023 with the inclusion criteria of articles from 2013 to 2023 that discussed the effect of photodynamic therapy as an adjunctive therapy in cases of periodontitis accompanied by diabetes mellitus. Five databases were used for the search method and four relevant studies were identified that stated that photodynamic therapy as an adjunctive therapy has a positive effect on the management of periodontitis in diabetic patients based on clinical and biochemical parameters. Conclusion: Photodynamic therapy showed positive results as adjunctive therapy in many cases of periodontitis with diabetes.